Prediction of Mutant mRNA Splice Isoforms by Information Theory‐Based Exon Definition. Issue 4 (21st February 2013) - Mucaki, Eliseos J.; Shirley, Ben C.; Rogan, Peter K.
<x xml:space="preserve">Abstract</x> Cryptic and exon skipping isoforms in mRNA produced by splicing mutations are predicted from the combined information contents and distribution of the splice sites defining these exons. Predictions of splicing mutations were highly concordant with published expression data. In silico exon definition analysis will contribute to streamlining assessment of abnormal and normal splice isoforms resulting from mutations. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>